2019
DOI: 10.3390/ijerph16234639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanoplastics on Freshwater Biofilm Microbial Metabolic Functions as Determined by BIOLOG ECO Microplates

Abstract: Nanoplastic (NP) contamination is becoming a pervasive issue as NPs, originating from microplastic particles, pose potentially harmful environmental impacts on aquatic ecosystems. The environmental hazards of NPs on microorganisms have been well documented in recent studies; however, little is known about their ecotoxicity effects on freshwater biofilms, which serve as important primary producers and decomposers and are highly connected with other ecosystem components. We investigated the effects of NPs on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Next, the suspension was added into the wells (150 µL) of the BIOLOG ECO microplate, and incubated at 25 • C for 7 days [50]. During the incubation, the absorbance value was determined at 590 every 12 h using a multifunctional enzyme label tester (Bio Tek, Winooski, VT, USA) for 7 to 10 days, and based on previous studies [51][52][53][54].…”
Section: Biolog Eco Microplate Test Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the suspension was added into the wells (150 µL) of the BIOLOG ECO microplate, and incubated at 25 • C for 7 days [50]. During the incubation, the absorbance value was determined at 590 every 12 h using a multifunctional enzyme label tester (Bio Tek, Winooski, VT, USA) for 7 to 10 days, and based on previous studies [51][52][53][54].…”
Section: Biolog Eco Microplate Test Methodsmentioning
confidence: 99%
“…Generally, the utilization of carbon sources was positively correlated with the meta bolic capacity of the corresponding microorganisms, which could be characterized b AWCD [51]. At present, the Biolog profiles are generally referred as Community Leve Physiological Profiles (CLPP) and have been widely used to explore the carbon metabo lism and degradation activity of microorganisms [ As shown in Figure 2c, in G1 and G2, there were significant differences between the COD concentrations of the G1 and G2 treatment groups during the whole test period (p < 0.05), and there was significant difference between the final value and initial value of COD concentration in the G1 and G2 treatment groups (p < 0.05).…”
Section: The Awcd Of All Carbon Sources In Sediment Microbial Communimentioning
confidence: 99%
See 1 more Smart Citation
“…Average well color development (AWCD) was measured using BIOLOG ECO microplates (Hayward, CA, USA) (see Supplementary Material SI ), which can be used to assess the ability of microbes to metabolize carbon sources. The details were given in our previous study [ 16 ]. Briefly, the biofilm samples were suspended and ultrasonicated.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Lu et al found that a low concentration (10 mg/L) of 100 nm plastic particles inhibited the reproduction of Chlorella pyrenoidosa, while a high-concentration (100 mg/L) exposure significantly increased the reproduction rate [ 15 ]. Previously, Guo et al studied the effect of nano-PS beads with different concentrations (1, 5 and 10 mg/L) on freshwater biofilm microbial metabolic functions [ 16 ], and Miao et al studied the acute effects of nano-PS beads with different particle sizes and concentrations on the functional enzymes of periphytic biofilms [ 10 ]. However, there is limited information about the effects of nanoplastics with different surface modifications on the microbial functions of freshwater biofilms.…”
Section: Introductionmentioning
confidence: 99%